Learning Human Skills An Experiental and Feflective Guide for Nurses - Third Edition 1995 - Antoinette Gmeiner (AOSIS, 1997)
Learning Human Skills is widely regarded as one of the key text for teaching and learning effective interpersonal, councelling and group skills at both student and practitioner level. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.